2016
DOI: 10.1155/2016/9298143
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Infection Complicated by Group A Beta-Hemolytic Streptococcal Retropharyngeal Abscess

Abstract: An unimmunized 19-month-old child presented with a retropharyngeal abscess and coincident varicella infection. The abscess resolved with operative drainage. This is the first published report of this connection, although varicella is known to be associated with abscesses in general. Practitioners should be aware that cervical abscesses may complicate varicella infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…24 By far, the most frequent manifestation of these superinfections is cellulitis, but cases have been reported of myositis, septic arthritis, craniofacial abscesses, and NF. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 By far, the most frequent manifestation of these superinfections is cellulitis, but cases have been reported of myositis, septic arthritis, craniofacial abscesses, and NF. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 25…”
Section: Discussionmentioning
confidence: 99%
“…24 By far, the most frequent manifestation of these superinfections is cellulitis, but cases have been reported of myositis, septic arthritis, craniofacial abscesses, and NF. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]25 NF as a sequela of chickenpox is well described in the medical literature. A systematic review of all reported NF cases in children identified 324 cases, with an association to VZV identified in 100 of them.…”
Section: Discussionmentioning
confidence: 99%
“…Особливу увагу привернули випадки рідкісних ускладнень ВВ -заглоткового абсцесу у дитини віком 19 міс [8], абсцесу легені у тримісячної дитини [4] та спінальних епідуральних абсцесів [9].…”
unclassified